Host-Mediated Post-Translational Prenylation of Novel Dot/Icm-Translocated Effectors of Legionella Pneumophila - Price, Christopher T.; Jones, Snake C.; Amundson, Karen E.; Abu Kwaik, Yousef (Frontiers in Microbiology, 2010)
The Dot/Icm type IV translocated Ankyrin B (AnkB) effector of Legionella pneumophila is modified by the host prenylation machinery that anchors it into the outer leaflet of the Legionella-containing vacuole (LCV), which is essential for biological function of the effector in vitro and in vivo. Prenylation involves the covalent linkage of an isoprenoid lipid moiety to a C-terminal CaaX motif in eukaryotic proteins enabling their anchoring into membranes. We show here that the LCV harboring an ankB null mutant is decorated with prenylated proteins in a Dot/Icm-dependent manner, indicating that other LCV membrane-anchored proteins are prenylated. In silico analyses of four sequenced L. pneumophila genomes revealed the presence of eleven other genes that encode proteins with a C-terminal eukaryotic CaaX prenylation motif. Of these eleven designated Prenylated effectors of Legionella (Pel), seven are also found in L. pneumophila AA100. We show that six L. pneumophila AA100 Pel proteins exhibit distinct cellular localization when ectopically expressed in mammalian cells and this is dependent on action of the host prenylation machinery and the conserved cysteine residue of the CaaX motif. Although inhibition of the host prenylation machinery completely blocks intra-vacuolar proliferation of L. pneumophila, it only had a modest effect on intracellular trafficking of the LCV. Five of the Pel proteins are injected into human macrophages by the Dot/Icm type IV translocation system of L. pneumophila. Taken together, the Pel proteins are novel Dot/Icm-translocated effectors of L. pneumophila that are post-translationally modified by the host prenylation machinery, which enables their anchoring into cellular membranes, and the prenylated effectors contribute to evasion of lysosomal fusion by the LCV.